2012
DOI: 10.1007/s11845-011-0792-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the prevalence of smoking and smoking cessation advice received by inpatients in a large teaching hospital in Ireland

Abstract: Background: The adverse effects of smoking are well documented and it is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 13 publications
(16 reference statements)
0
14
2
Order By: Relevance
“…These findings suggest that organisational and attitudinal change is needed, and smoke-free policies may help address this issue. A previous Irish study in 2011 reported that only 44% of current/recent smokers had received smoking cessation advice from a health professional in the past year (Bartels et al, 2011). However, this was a single-site study, and the site examined in this study did not have the smoke-free policy in place at the time of the survey.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…These findings suggest that organisational and attitudinal change is needed, and smoke-free policies may help address this issue. A previous Irish study in 2011 reported that only 44% of current/recent smokers had received smoking cessation advice from a health professional in the past year (Bartels et al, 2011). However, this was a single-site study, and the site examined in this study did not have the smoke-free policy in place at the time of the survey.…”
Section: Introductionmentioning
confidence: 86%
“…Cronbach's alpha for the FTND in this sample was 0.77. Attitudes to smoking and cessation were examined using questions developed as part of previous work in order to facilitate direct comparison (Bartels et al, 2011). Data were collected using an encrypted iPad device.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, despite hospitalization being a teachable moment for smoking cessation, healthcare professionals advise patients to quit less often than they should (1,61,62).…”
Section: Treatments and Hospitalizationmentioning
confidence: 99%
“…Perceived or assumed patient resistance 21,22 and a tendency to assume patients are not motivated 25 have also emerged in the research as barriers in spite of numerous studies showing a positive attitude amongst patients to smoking cessation advice. Interventions should address this knowledge gap by making efforts to educate healthcare staff about the often positive attitudes of smoking patients towards quitting 26,27 . Additional barriers include HCPs not regarding smoking cessation counselling as part of their role 23 and lack of reimbursement [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%